Preservación de la ceguera en los recién nacidos en la provincia de Buenos Aires (República Argentina) - Argüello, Diego M. (1937)
The problem of the prevention of blindness in the newborns has been faced in a practical form and in all its amplitude in the Province of Buenos Aires. Measures have been adopted tending to illustrate to the people by means of affliches, lectures and radiotelephone about the dangers to which the newborns are exposed and the form to avoid them. The Civil Registers in momment of celebrating marriages and during the time of recording births, deliver instructions clearly and precisely relative to the prevention of blindness, and besides, the material is appropriated for the parents to apply the method of Credé, where there is no midwife. The disposable material used consist of a carton box containing 2 % (two per cent) silver nitrate solution in a glass ampulle of caramel colour with double point, and a capillary glass tube with a piece of rubber united at one of its ends, and a small file, accompanied also by graphical instructions as to its use. The chiefs of the same note in a design in the momment of elaborating the act (six to light days after birth) whether the child has or not the eyes diseased, thus carrying a statistics, which permits the local board of health to verify the existence of purulent ophthalmia and to lend adequate medical assistance. The obligatory method of Credé was sanctioned by law on 2nd of October 1936, making it obligatory for the midwives to instill a drop of two per cent silver nitrate solution in the conjunctiva of both eyes of the newborns, in order to prevent blindness (art. 67). Article 68, establishes that the midwives who violate this disposition, will suffer a fine of one hundred to three hundred pesos legal money, without being subject to criminal proceedings.